Anti-Toxoplasma Activity of Estragole and Thymol in Murine Models of Congenital and Noncongenital Toxoplasmosis - Oliveira, Cláudio Bruno Silva de; Meurer, Ywlliane S.R.; Medeiros, Thales L.; Pohlit, Adrian Martin; Silva, Murilo Vieira; Mineo, Tiago W.P.; Andrade Neto, Valter Ferreira de (Journal of Parasitology, 2016)
Toxoplasmosis is caused by Toxoplasma gondii, an obligatory intracellular protozoan. Normally benign, T. gondii infections can cause devastating disease in immunosuppressed patients and through congenital infection of newborn babies. Few prophylactic and therapeutic drugs are available to treat these infections. The goal of the present study was to assess the anti-Toxoplasma effects in a congenital and noncongenital model of toxoplasmosis (using ME49 strain), besides assessing immunological changes, in vitro cytotoxicity, and in vivo acute toxicity of commercial estragole and thymol. The congenital experimental model was used with intermediate stages of maternal infection. The serum levels of immunoglobulin (Ig)M, IgG, interleukin (IL)-10, IL-12, and interferon-gamma (IFN-γ) were quantified from infected and treated C57Bl/6 mice. Estragole and thymol respectively exhibited low to moderate in vivo toxicity and cytotoxicity. Animals treated with estragole showed high IFN-γ and strong type 1 helper T cell response. Both compounds were active against T. gondii ME49 strain. Furthermore, orally administered estragole in infected pregnant mice improved the weight of offspring compared with untreated controls. Subcutaneous administration of both compounds also increased the weight of mouse offspring born to infected mothers, compared with untreated controls. Estragole and thymol display important anti-Toxoplasma activity. Further studies are needed to elucidate the mechanism of action of these compounds. © American Society of Parasitologists 2016.
Keywords: Estragole; Gamma Interferon; Immunoglobulin G; Immunoglobulin M; Interleukin-10; Interleukin-12; Thymol; Anisole Derivative; Antiinfective Agent; Cytokine; Estragole; Immunoglobulin G; Immunoglobulin M; Protozoon Antibody; Thymol; Anti-microbial Activity; Body Mass; Cells And Cell Components; Disease Treatment; Drug; Immune Response; Immunoassay; Infectious Disease; Phenolic Compound; Pregnancy; Protozoan; Rodent; Toxicity; Acute Toxicity; Animals Experiment; Animals Model; Comparative Study; Congenital Toxoplasmosis; Controlled Study; Cytotoxicity; Cytotoxicity Assay; Drug Mechanism; Enzyme-linked Immunosorbent Assay; Female; Hela Cell Line; Helper Cell; Hep-g2 Cell Line; Human; Human Cell; In Vitro Study; In Vivo Study; Mouse; Nonhuman; Survival Rate; Toxicity Testing; Toxoplasma Gondii; Toxoplasmosis; Animals; Toxoplasmosis, Animals; Blood; Brain; C57bl Mouse; Cell Culture; Drug Effect; Hep-g2 Cell Line; Immunology; Parasitology; Peritoneum Macrophage; Pregnancy; Pregnancy Complication; Toxoplasma; Animalsia; Murinae; Mus; Protozoa; Toxoplasma; Toxoplasma Gondii; Animal; Anisoles; Anti-infective Agents; Antibodies, Protozoan; Brain; Cells, Cultured; Cytokines; Female; Hela Cells; Hep G2 Cells; Humans; Immunoglobulin G; Immunoglobulin M; Macrophages, Peritoneal; Mice; Mice, Inbred C57bl; Pregnancy; Pregnancy Complications, Parasitic; Thymol; Toxoplasma; Toxoplasmosis, Animals